Effect of Early Feeding with Synbiotics on Nutrient Digestibility, Carcass Characteristics and Gut Morphology of Broiler Chicken - Patel, Minnat M; Vahora, Safimahmad G; Rajpura, Rais M; Vansola, Jignesh H; Gameti, Chintan B; Desai, Dharmik M (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study was aimed to assess the effect of early feeding with synbiotics on nutrient digestibility, carcass characteristics and gut morphology of broiler chicken. A total of 144 day-old chicks were randomly assigned to four treatment groups, each comprising 9 birds per replicate, with 4 replicates per group. In Control group, birds received synbiotics (Probiotics + Prebiotics) in water and pre-starter feed upon arrival at the farm for 24 h. The Negative Control group received water and pre-starter feed without synbiotics. In Transport group, birds got synbiotics via beak dip at the hatchery and continued with synbiotics at the farm for 24 h. In the Treatment On-farm group (OF), birds received synbiotics immediately after hatching on the farm for 24 h. Early access to feed and synbiotics added water resulted in numerically higher retention of dry matter and organic matter in the OF group compared to the Control, Negative Control and Transport groups. The average daily positive nitrogen balance (g/bird) was significantly higher (p<0.05) in the Negative Control group compared to the Control, Transport and OF groups. The weight of gizzard, giblet, small intestine and large intestine were found significantly higher (p<0.05) in the OF group. The villus height of duodenum at the age of 21 and 42 days was significantly higher in early feeding with synbiotics in OF group. Livability remained statistically similar throughout the experimental period. The result suggests that early feeding with synbiotics to newly hatched chicks as soon as they hatched on the farm increases the weight of gizzard, giblet and intestine with better gut health.